Olfactory sensitivity to conspecific bile fluid and skin mucus in the European eel Anguilla anguilla (L.) - Huertas, Mar (2014)
The present study assessed the olfactory potency of conspecific bile fluid and skin mucus in the European eel Anguilla anguilla by the electro-olfactogram. Immature males showed high olfactory sensitivity to conspecific bile, giving large amplitude responses in a concentrationdependent manner with estimated thresholds of detection of <1:107 (n = 6). Mucus also proved to contain highly potent odorants with thresholds of detection of c. 1:106 (n = 6). Crude solidphase extraction of bile fluid (C-18 and C-2/ENV+ cartridges) showed that the majority of olfactory activity in bile fluid was contained in the eluate of C-18 cartridges (n = 6). There were quantitative differences, however, between the sexes; female bile fluid had a higher proportion of activity in this fraction. Similar solid-phase extraction of mucus showed that it contains a higher proportion of odorants in the C-18 filtrate than bile fluid. Mucus from mature eels, however, had a higher proportion of olfactory activity in the eluate than immature fish (n = 6). Cross-adaptation experiments suggest that there are qualitative differences in the odorants contained in bile and mucus depending on both the sex and state of sexual maturation of the donor (n = 6). These results are consistent with a role for chemical communication in the reproduction of the European eel and suggest that both bile and mucus are potential sources of the odorants involved.